Pelatihan Pembelajaran Matematika Berbasis Deep Learning dan Teknologi untuk Guru Sekolah Dasar - Ahmad, Syafri; Zen, Zelhendri; Hamimah, Hamimah; Masniladevi, Masniladevi; Kenedi, Ary Kiswanto; Mardin, Asna (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service program aimed to improve teachers’ competence in designing and implementing mathematics learning based on deep learning and technology to support character education at SD Gugus VI Koto Tangah, Padang City. The main problems addressed were teachers’ limited understanding of meaningful learning approaches and the low use of digital media in the classroom. The methods used included training, workshops, teaching simulations, and classroom implementation assistance. The results showed a significant increase in teachers’ understanding based on pre- and post-test scores, as well as the successful development of lesson plans and digital teaching media that integrate character values. Classroom implementation indicated improved student engagement and better learning interaction. This program demonstrates that deep learning-based approaches combined with technology are effective at the elementary level and can strengthen character education in a contextual and applicable way.